Left ventricular assist device in the presence of subcutaneous implantable cardioverter defibrillator: data from a multicenter experience - Migliore, Federico; Schiavone, Marco; Pittorru, Raimondo; Forleo, Giovanni B.; De Lazzari, Manuel; Mitacchione, Gianfranco; Biffi, Mauro; Gulletta, Simone; Kuschyk, Jürgen; Dall'Aglio, Pietro Bernardo; Rovaris, Giovanni; Tilz, Roland; et al. (International journal of cardiology, 2024)
Background - Left ventricular assist devices (LVADs) are an increasingly used strategy for the management of patients with advanced heart failure (HF). Subcutaneous implantable cardioverter defibrillator (S-ICD) might be a viable alternative to conventional ICDs with a lower risk of short- and long-term of device-related complications and infections.The aim of this multicenter study was to evaluate the outcomes and management of S-ICD recipients who underwent LVAD implantation. - Methods - The study population included patients with a preexisting S-ICD who underwent LVAD implantation for advanced HF despite optimal medical therapy. - Results - The study population included 30 patients (25 male; median age 45 [38-52] years).The HeartMate III was the most common LVAD type. Median follow-up in the setting of concomitant use of S-ICDs and LVADs was 7 months (1-20).There were no reports of inability to interrogate S-ICD systems in this population. Electromagnetic interference (EMI) occurred in 21 (70%) patients. The primary sensing vector was the one most significantly involved in determining EMI. Twenty-seven patients (90%) remained eligible for S-ICD implantation with at least one optimal sensing vector. The remaining 3 patients (10%) were ineligible for S-ICD after attempts of reprogramming of sensing vectors. Six patients (20%) experienced inappropriate shocks (IS) due to EMI. Six patients (20%) experienced appropriate shocks. No S-ICD extraction because of need for antitachycardia pacing, ineffective therapy or infection was reported. - Conclusions - Concomitant use of LVAD and S-ICD is feasible in most patients. However, the potential risk of EMI oversensing, IS and undersensing in the post-operative period following LVAD implantation should be considered. Careful screening for EMI should be performed in all sensing vectors after LVAD implantation.
Online verfügbar: 23. Januar 2024, Artikelversion: 19. Februar 2024
Gesehen am 03.02.2025